2015
DOI: 10.1001/jamasurg.2015.74
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mandatory Centers of Excellence Designation on Demographic Characteristics of Patients Who Undergo Bariatric Surgery

Abstract: The COE certification requirement by CMS did not appear to limit access to bariatric surgery. Future studies should determine whether CMS's recent (2013) change in policy (ie, removing the mandatory COE certification for bariatric surgical insurance coverage) might sacrifice patient safety without addressing the real cause of limited access to health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Although several studies reporting that patients without private insurance were significantly underrepresented in bariatric surgery [ 31 , 32 ], our finding of the improved access to bariatric surgery for Medicare or Medicaid beneficiaries is encouraging. In a national representative dataset, the percentage of bariatric procedures covered by Medicare rose from 8.5% in 2006 to 16.3% in 2011 [ 33 ], while increasing from 15.8% in 2011 to 19.2% in 2014 in our study. One recent study also reported that patients covered by Medicare or Medicaid are more likely to undergo gastric bypass than privately insured patients [ 34 ].…”
Section: Discussionmentioning
confidence: 50%
“…Although several studies reporting that patients without private insurance were significantly underrepresented in bariatric surgery [ 31 , 32 ], our finding of the improved access to bariatric surgery for Medicare or Medicaid beneficiaries is encouraging. In a national representative dataset, the percentage of bariatric procedures covered by Medicare rose from 8.5% in 2006 to 16.3% in 2011 [ 33 ], while increasing from 15.8% in 2011 to 19.2% in 2014 in our study. One recent study also reported that patients covered by Medicare or Medicaid are more likely to undergo gastric bypass than privately insured patients [ 34 ].…”
Section: Discussionmentioning
confidence: 50%
“…Having in view the large number of bariatric procedures performed each year over the past 15 years, national and regional organization of bariatric surgery now constitutes a major issue. Indeed, it needs to plan in terms of access to expert care in each region, [12] individual choice of the most appropriate procedure, supply adapted to the epidemiological context, and health system funding. [3] It should also specifically structure care for teenagers or elderly patients, as well as in case of reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 This suggests the incidence of spine issues as a serious side effect of obesity. Khoueir et al 16 showed that weight reduction after bariatric surgery is potentially associated with a lessening of preexisting back pain.…”
Section: Discussionmentioning
confidence: 99%